Genetic Deletion or Pharmacological Inhibition of Cyclooxygenase-2 Reduces Blood-Brain Barrier Damage in Experimental Ischemic Stroke - Yang, Changjun; Yang, Yi; DeMars, Kelly M.; Rosenberg, Gary A.; Candelario-Jalil, Eduardo (Frontiers in Neurology, 2020)
Cyclooxygenase (COX)-2 and matrix metalloproteinase (MMP)-9 are two crucial mediators contributing to blood-brain barrier (BBB) damage during cerebral ischemia. However, it is not known whether MMP-9 activation is involved in COX-2-mediated BBB disruption in ischemic stroke. In this study, we hypothesized that genetic deletion or pharmacological inhibition of COX-2 reduces BBB damage by reducing MMP-9 activity in a mouse model of ischemic stroke. Male COX-2 knockout (COX-2-/-) and wild-type (WT) mice were subjected to 60 min of middle cerebral artery occlusion (MCAO) followed by 24 h of reperfusion. Genetic deletion of COX-2 or post-ischemic treatment with CAY10404, a highly selective COX-2 inhibitor, significantly reduced BBB damage and hemorrhagic transformation, as assessed by immunoglobulin G (IgG) extravasation and brain hemoglobin (Hb) levels, respectively. Immunoblotting analysis showed that tight junction proteins (TJPs) zonula occludens (ZO)-1 and occludin as well as junctional adhesion molecule-A (JAM-A) and the basal lamina protein collagen IV were dramatically reduced in the ischemic brain. Stroke-induced loss of these BBB structural proteins was significantly attenuated in COX-2-/- mice. Similarly, stroke-induced loss of ZO-1 and occludin was significantly attenuated by CAY10404 treatment. Ischemia-induced increase in MMP-9 protein levels in the ipsilateral cerebral cortex was significantly reduced in COX-2-/- mice. Stroke induced a dramatic increase in MMP-9 enzymatic activity in the ischemic cortex, which was markedly reduced by COX-2 gene deficiency or pharmacological inhibition with CAY10404. Levels of myeloperoxidase (MPO, an indicator of neutrophil infiltration into the brain parenchyma), neutrophil elastase (NE), and lipocalin-2 (LCN2, also known as neutrophil gelatinase-associated lipocalin), measured by western blot and specific ELISA kits respectively, were markedly increased in the ischemic brain. Increased levels of markers for neutrophil infiltration were significantly reduced in COX-2-/- mice compared with WT controls following stroke. Altogether, neurovascular protective effects of COX-2 blockade are associated with reduced BBB damage, MMP-9 expression/activity and neutrophil infiltration. Our study shows for the first time that MMP-9 is an important downstream effector contributing to COX-2-mediated neurovascular damage in ischemic stroke. Targeting the COX-2/MMP-9 pathway could represent a promising strategy to reduce neuroinflammatory events in order to preserve the BBB integrity and ameliorate ischemic stroke injury.